The Impact of Simple Layering and Layer Rotation Design on the Natural Vibration Performance of Grid Beetle Elytron Plates - Youlong Wang; Chenwei Guo; Yuxiang Cai; Yiheng Song (Proceedings)
This study analyzes the natural vibration characteristics of grid beetle elytron plates (GBEPs), a type of laminated plate inspired by the sandwich structure of beetle forewings, under different angles of rotations [...]